A Loop-Line Antenna with Enhanced Bandwidth of Circular Polarization - Kazuhide Hirose; Motoshi Nakatsu; Hisamatsu Nakano (International Journal of Antennas and Propagation)
We investigate a circularly polarized (CP) transmission-line antenna composed of loop radiation elements, called a loop-line antenna. To enhance the CP wave bandwidth, an isolated loop radiation element is first analyzed using the method of moments. It is found that a CP wave bandwidth for a 3 dB axial-ratio criterion has a maximum value of 8%. On the basis of the analysis results, we design the loop-line antenna. It is found that the antenna shows a CP wave bandwidth of 6%, which is twice as wide as that of a conventional loop-line antenna. The analysis results are verified with experimental ones. In addition, a condition for wideband CP radiation is discussed and found to be a composite radiation element consisting of two CP loops.